Testing for Construct Bias in the Differential Ability Scales, Second Edition: A Comparison Among African American, Asian, Hispanic, and Caucasian Children. (October 2018) - Trundt, Katherine M.; Keith, Timothy Z.; Caemmerer, Jacqueline M.; Smith, Leann V.
Individually administered intelligence measures are commonly used in diagnostic work, but there is a continuing need for research investigating possible test bias among these measures. One current intelligence measure, the Differential Ability Scales, Second Edition (DAS-II), is a test with growing popularity. The issue of test bias, however, has not been thoroughly investigated with the DAS-II. The current study investigated whether the DAS-II demonstrates systematic construct bias when used with children from three racial and ethnic groups—African American, Asian, and Hispanic—when compared to non-Hispanic Caucasian children. Multi-group confirmatory factor analyses with data from the DAS-II standardization sample were used to assess whether the constructs and measurement of constructs were invariant across groups. Results indicate cross-group internal structure validity in the DAS-II, and thus a lack of construct bias. Minor differences were found, but these differences do not affect the calculation of composite scores on the DAS-II and thus would not result in unfair scoring for the groups involved. Results of this study support the appropriateness of the DAS-II for clinical use with these racial and ethnic groups.